1975
DOI: 10.1159/000264754
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fluorescence in the Human Cataractous Lens

Abstract: Normal and cataractous lenses contain a highly fluorescent yellow protein which is insoluble in water but soluble in 7 m urea containing 0.01 m mercaptoethanol. The amount of this protein increases with the development of cataracts and this is accompanied by a decrease in the water-soluble protein content of the lens. The protein has a molecular weight of over 80,000 in the presence of 7 m urea and mercaptoethanol. It appears to be a derivative of the sub-units of the soluble crystalline cross-linked through c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Circumstantial evidence indicates that chronic exposure of human eyes to ambient near-UV radiation may cause photocatalyzed reactions that initiate the formation of nuclear senile cataract with a concomitant production of fluorescent chromophors (5)(6)(7)(8). The examples of these reactions are the photooxidation of tryptophan (9,10) and the generation of singlet oxygen by UV and photosensitizers endogenous to the human lens (11).…”
mentioning
confidence: 99%
“…Circumstantial evidence indicates that chronic exposure of human eyes to ambient near-UV radiation may cause photocatalyzed reactions that initiate the formation of nuclear senile cataract with a concomitant production of fluorescent chromophors (5)(6)(7)(8). The examples of these reactions are the photooxidation of tryptophan (9,10) and the generation of singlet oxygen by UV and photosensitizers endogenous to the human lens (11).…”
mentioning
confidence: 99%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 (11). Four fractions were taken for racemization analyses.…”
mentioning
confidence: 99%
“…That is followed by fluctuation in the protein content and thereby in the refractive index which increases the light scatter (Philipson 1973;Duncan et al 1989Duncan et al , 1997. In nuclear cataract, there is increase in selective spectral absorption, in pigmented chromophores and in cross-linked protein aggregates found in the nuclear region (Philipson 1973;Augusteyn 1975). It has been proposed that the decreased transmission of visible light in the aging lens and in nuclear cataract is mainly due to the accumulation of lens fluorogens rather than configurational changes of the lens pro-teins as seen in cortical cataracts (Lerman & Borkman 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The lens fluorogens are responsible to a significant degree for the increasing yellow coloration of the lens with age (Augusteyn 1975;Lerman & Borkman 1976). We have developed a technique to measure blue-green autofluorescence (AF) of the lens and showed that it increases with age and with the degree of nuclear cataract (Siik et al 1991(Siik et al , 1993.…”
mentioning
confidence: 99%